2021
DOI: 10.3389/fmed.2021.713262
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Risk of Childhood Asthma at Age 6 With Maternal Allergic or Immune-Mediated Inflammatory Diseases: A Nationwide Population-Based Study

Abstract: Objective: This study aimed to assess the associations of the risk of asthma diagnosed in children aged 6 years or younger and having maternal immune-mediated inflammatory diseases (IMIDs), including systemic lupus erythematosus (SLE), systemic sclerosis (SSc), inflammatory myositis, rheumatoid arthritis (RA), Sjögren's syndrome (SS), ankylosing spondylitis (AS), and autoimmune thyroiditis.Methods: A total of 628,878 singleton newborns documented in 2006–2009 and followed up for at least 6 years were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
1
0
0
Order By: Relevance
“…Therefore, the status of maternal immune system was linked to childhood asthma. Yang et al reported an elevated chance of asthma in children born to mothers with maternal RA [ 41 ], which was consistent with our analysis.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, the status of maternal immune system was linked to childhood asthma. Yang et al reported an elevated chance of asthma in children born to mothers with maternal RA [ 41 ], which was consistent with our analysis.…”
Section: Discussionsupporting
confidence: 93%